The Effects of Integrated Training Program on Self-Leadership Vocational Certificate Students - Bophimai, Uraiwan; Chanvirat , Waradee (Ratchaphruek Journal, 2021)
This research was the study of the results of using the self-leadership after using the integrated training program. The objectives were: 1) To compare self-leadership before and after training; and 2) To compare self-leadership after training between the experimental group and control group. The sample used in this research were the vocational certificate students from a college in Nakhon Ratchasima Province.. The purposive sampling of 20 students (10for experimental and 10 for control) with Moderate levels below 3.20 of self-leadership skills were selected. Before and after data was collected on all participating students. Data was collected by using a measure self-leadership with a confidence factor of .861. The students in the experimental group attended an integrated training program of 2 days, 6 hours a day. The control group students did not participate in the training. The data collected was analyzed by mean, standard deviation, and t-test. The results were found that: 1) The post-test scores of the experimental group had statistically higher at the .01 level. 2) The experimental group had statistically significant higher scores than the control group at the .01 level.